A matrix-based IRLS algorithm for the least lp-norm design of 2-D FIR filters - Zhao, Ruijie (2020)
Fast design of two-dimensional FIR filters in the least lp-norm sense is investigatedin this brief. The design problem is first formulated in a matrix form and then solved by amatrix-based iterative reweighted least squares algorithm. The proposed algorithm includestwo loops: one for updating the weighting function and the other for solving the weightedleast squares (WLS) subproblems. These WLS subproblems are solved using an efficientmatrix-based WLS algorithm, which is an iterative procedure with its initial iterative matrixbeing the solution matrix in the last iteration, resulting in a considerable CPU-time saving.Through analysis, the new algorithm is shown to have a lower complexity than existingmethods. Three design examples are provided to illustrate the high computational efficiencyand design precision of the proposed algorithm.